Kamilla Łozowska-Marcinkowska, Sprawy niewieście. Problematyka czasopism kobiecych Drugiej Rzeczypospolitej, Wydawnictwo Poznańskie, Poznań 2010, ss. 298 - Nowak-Kluczyński, Konrad (Biuletyn Historii Wychowania, 2011)
Kamilla Łozowska-Marcinkowska, Sprawy niewieście. Problematyka czasopism kobiecych Drugiej Rzeczypospolitej, Wydawnictwo Poznańskie, Poznań 2010, ss. 298